Next Generation Sequencing (NGS) for Cyanobacterial study in Agung and Sunter Barat Lakes, North Jakarta, Indonesia - DIAN HENDRAYANTI; NINING BETAWATI PRIHANTINI; FITRIA NINGSIH; FADHLURAHMAN MAULANA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Hendrayanti D, Prihantini NB, Ningsih F, Maulana F. 2023. Next Generation Sequencing (NGS) for Cyanobacterial study in Agung and Sunter Barat Lakes, North Jakarta, Indonesia. Biodiversitas 24: 1117-1124. The Next Generation Sequences (NGS) is one of the established metabarcoding methods for analyzing microbial communities. Investigation of the cyanobacterial community in eutrophic freshwater habitats is important, especially for those known as toxic-released cyanobacteria. This study aimed to analyze the structure community of cyanobacteria in Agung and Sunter Barat Lakes in North Jakarta, DKI Jakarta Province using the NGS method. The physico-chemical parameters were also measured. Sampling plots were selected by purposive sampling method. The result of the study successfully analyzed the bacterial community structure and portrayed the dominancy of the cyanobacterial population on the two lakes. Several cyanobacteria genera previously reported in 2008 research were found, including Arthrospira and Planktothrix. The diversity index in Agung Lake (4.7) was higher than in Sunter Barat Lake (3.7). Two dominant populations were found, which were Raphidiopsis (in Agung Lake) and Planktothrix (in Sunter Barat Lake). Both genera have been acknowledged as toxin-releasing cyanobacteria, which could be harmful to the water-biotic community as well as human health. The presence of potentially toxic cyanobacteria in the recreation area of Agung Lake should be taken into consideration for biomonitoring management.